Impact of personalized diet and probiotic supplementation on inflammation, nutritional parameters and intestinal microbiota – The "RISTOMED project": Randomized controlled trial in healthy older people. Issue 4 (August 2015) - Valentini, Luzia; Pinto, Alessandro; Bourdel-Marchasson, Isabelle; Ostan, Rita; Brigidi, Patrizia; Turroni, Silvia; Hrelia, Silvana; Hrelia, Patrizia; Bereswill, Stefan; Fischer, André; Leoncini, Emanuela; Malaguti, Marco; et al.
Summary Objectives To assess the impact of a personalized diet, with or without addition of VSL#3 preparation, on biomarkers of inflammation, nutrition, oxidative stress and intestinal microbiota in 62 healthy persons aged 65–85 years. Design Open label, randomized, multicenter study. Primary endpoint: High-sensitivity C-reactive protein. Setting Community. Interventions Eight week web-based dietary advice (RISTOMED platform) alone or with supplementation of VSL#3 (2 capsules per day). The RISTOMED diet was optimized to reduce inflammation and oxidative stress. Measurements Blood and stool samples were collected on days 1 and 56. Results Diet alone reduced ESR (p = 0.02), plasma levels of cholesterol (p < 0.01) and glucose (p = 0.03). Addition of VSL#3 reduced ESR (p = 0.05) and improved folate (p = 0.007), vitamin B12 (p = 0.001) and homocysteine (p < 0.001) plasma levels. Neither intervention demonstrated any further effects on inflammation. Subgroup analysis showed 40 participants without signs of low-grade inflammation (hsCRP<3 mg/l, subgroup 1) and 21 participants with low-grade inflammation at baseline (hsCRP≥3 mg/l, subgroup 2). In subgroup 2 addition of VSL#3 increased bifidobacteria (p = 0.005) in more participants and improved both folate (p = 0.015) and vitamin B12 (p = 0.035) levels compared with subgroup 1. The increases were positively correlated to the change in the bifidobacteria concentration for folate (p = 0.023) and vitamin B12 (p = 0.001). As expected change in homocysteine correlated negatively to change in folate (r = −0.629, p = 0.002) and vitamin B12 (r = −0.482, p = 0.026). Conclusions Addition of VSL#3 increased bifidobacteria and supported adequate folate and vitamin B12 concentrations in subjects with low-grade inflammation. Decrease in homocysteine with VSL#3 was clinically relevant. suggesting protective potentials for aging-associated conditions, e.g. cardiovascular or neurological diseases. ClinicalTrials.gov: NCT01069445–NCT01179789.